Rethinking Islamic epistemology and integration of knowledge in sustaining Islamic intellectualism in the era of AI driven inquiry - Surajudeen, Ahmad Tijani; Nordin, Norfadelah; Ibrahim, Abdul Qahhar (Journal of Islamic, Social, Economics and Development, 2025)
This study critically explores Islamic epistemology and the integration of knowledge as foundational frameworks for sustaining Islamic intellectualism in the era of AI driven inquiry. Through a critical content analysis of classical Islamic epistemic sources namely, the Qur’an, Sunnah, and the intellectual heritage of scholars such as al-Ghazālī, Ibn Sīnā, and Ibn Khaldūn alongside contemporary discourses on artificial intelligence and digital knowledge production, the study interrogates how epistemological dualism between revealed and acquired knowledge has been historically negotiated and can be harmonized today. The analysis reveals that while AI driven systems promote unprecedented access to knowledge, they also risk epistemic reductionism by privileging algorithmic rationality over divine wisdom. Islamic intellectualism, however, thrives on the holistic synthesis of rational (ʿaql) and revelatory (naql) sciences, emphasizing ethical intention (niyyah), spiritual insight (maʿrifah), and moral accountability (taklīf) in the pursuit of knowledge. The study argues that integrating Islamic epistemology with AI frameworks requires a paradigm shift one that re-centers tawḥīd (divine unity) as the organizing principle of knowledge, ensuring that technological advancement remains subordinated to moral and spiritual purpose. The findings suggest that the sustainability of Islamic intellectualism in the digital age depends on fostering epistemic humility, critical ethical awareness, and interdisciplinary dialogue between traditional scholars and AI technologists. The paper suggests that a maqāṣid al-sharīʿah oriented approach to digital knowledge ethics should be advocated for, by situating AI within a value-based epistemological continuum.